Request Strategies used by Male and Female Participants on Ome TV - Wuriy Handayani; Ninuk Lustyantie; Ifan Iskandar (Budapest International Research and Critics University, 2022)
The research on male and female languages is an interesting issue that has emerged not only in Indonesia but also in other countries. This study aims to clarify request strategies used by men and women and the reasons why they use it. It presents three separate studies, namely pragmatics, sociolinguistics and technology. Content analysis is used in this research and the data are five Ome TV videos taken from You Tube. The participants in those videos are males and females came from different cultural background. The findings show different request strategies used by male and female because of several reasons. To summarize, male and female use different request strategies that lead to different gender characteristic.